2014
DOI: 10.1002/ajoc.201402060
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I)‐Promoted Alkylation of Alkenylbenzyldimethylsilanes

Abstract: Palladium‐catalyzed cross‐coupling of acid‐ and base‐unstable heteroatom‐functionalized organosilanes and C(sp2)X electrophiles such as aryl and alkenyl (pseudo)halides has been extensively studied. In contrast, little is known about the coupling between unactivated alkenyltrialkylsilanes and C(sp3)X electrophiles. Herein, the copper(I)‐promoted coupling of chromatographically stable alkenylbenzyldimethylsilanes with unreactive alkyl halides as well as allyl and benzyl halides is described. The reaction proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 33 publications
0
13
1
4
Order By: Relevance
“…55 The authors later showed that the vinylsilicon reagents coupled with primary alkyl and benzyl halides without the need for coordinationassisted activation by alkoxide when the reaction was conducted in DMF in the presence of stoichiometric amounts of CuI•P(OEt) 3 as a catalyst and Bu 4 NF•(tBuOH) 4 as a fluoride source (Scheme 26). 56 Similarly, Riant and co-workers also disclosed that their reaction protocol developed for coupling vinyltriethoxysilanes with alkynyl bromide (Scheme 24) could also utilise benzyl bromides as electrophiles (Scheme 27). 57 These couplings with primary alkyl and benzyl electrophiles are likely to proceed via a traditional S N 2-type mechanism analogous to the reactions of similar electrophiles with Grignard and organoboron reagents with Cu-catalysts discussed above.…”
Section: Coupling With Organosilicon Reagentsmentioning
confidence: 99%
“…55 The authors later showed that the vinylsilicon reagents coupled with primary alkyl and benzyl halides without the need for coordinationassisted activation by alkoxide when the reaction was conducted in DMF in the presence of stoichiometric amounts of CuI•P(OEt) 3 as a catalyst and Bu 4 NF•(tBuOH) 4 as a fluoride source (Scheme 26). 56 Similarly, Riant and co-workers also disclosed that their reaction protocol developed for coupling vinyltriethoxysilanes with alkynyl bromide (Scheme 24) could also utilise benzyl bromides as electrophiles (Scheme 27). 57 These couplings with primary alkyl and benzyl electrophiles are likely to proceed via a traditional S N 2-type mechanism analogous to the reactions of similar electrophiles with Grignard and organoboron reagents with Cu-catalysts discussed above.…”
Section: Coupling With Organosilicon Reagentsmentioning
confidence: 99%
“…The controlling element is the silyl group which is at the same time a handle for the installation of another 1° alkyl group. Tsubouchi and co‐workers developed a copper‐promoted protocol for the cross‐coupling of BnMe 2 Si‐substituted vinylsilanes and alkyl electrophiles [9] . To demonstrate the potential synthetic utility of our chiral vinylsilanes, we had included the BnMe 2 Si‐substituted allylic bromides rac ‐ 7 a and rac ‐ 7 b into our scope.…”
Section: Methodsmentioning
confidence: 99%
“…atom in the allylic position (Scheme 1, bottom). [8] The silyl group attached to a C(sp 2 ) carbon atom could then be a placeholder for another 18 alkyl group, [9] thereby providing a two-step regioselective access to exclusively alkyl-substituted acyclic allylic systems with excellent diastereo-and high enantiocontrol (Scheme 2, bottom). [10] For the optimization of the reaction conditions, we chose silylated allylic bromide rac-1 a as a mixture of regioisomers (a:g = 53:47) [11] and 2.0 equiv of primary alkylzinc bromide 2 a as model substrates (Table 1).…”
Section: Enantioselectivenickelcatalysisinvolvingradicalintermedi-mentioning
confidence: 99%
“…Alkyl- and arylboron reagents have also been shown to couple with primary alkyl halides and pseudohalides, which proceed via a traditional S N 2 process . Recently, Riant and Takeda , also disclosed Cu-catalyzed reactions of aryl and vinylsilicon reagents with alkyl, benzyl, and alkynyl halides . Despite these tremendous efforts in recent times in showcasing the effectiveness of Cu catalysts for cross-coupling various organometallic reagents with organohalides, a general reaction that encompases a wide substrate scope is still far from reality.…”
Section: Introductionmentioning
confidence: 99%